Penguatan karakter dalam pembelajaran berbicara dengan menggunakan strategi belajar bahasa - Iis Lisnawati; Sumarti Sumarti (Aksara: Jurnal Bahasa dan Sastra, 2023)
The character that must be possessed by graduates, especially prospective educators, is complex. Moreover, graduates as prospective educators must not only have the graduate character as predetermined, but also transfer these characters to their students in the future. Therefore, a strategy is needed that makes it easier for students/learners as prospective educators to have the expected character. This study describes character strengthening through speaking learning with using Language Learning Strategies (LLS). This study uses the method of literature study. Character strengthening can be carried out in each LLS stage according to the selected SBB. In other words, strengthening character according to the goals and functions of education, 21st Century HR, Industrial Revolution 4.0, Social Revolution 5.0, and even Merdeka Learning-Independence Campus can be carried out in an integrated manner in speaking learning with using LLS. Keywords: character, speaking learning, Language Learning Strategies